Sistema de ultrassom para auxílio na identificação do risco de fraturas devido à osteoporose: SUSDO - Cruz, Cristiana Carla (2012)
This document presents the development of an ultrasound system to identify the risk of fractures due to osteoporosis. The system performs ultrasound scanning of the calcaneus region through the mode transmission-reception. The parameters broadband ultrasound attenuation (BUA) and speed of sound (SOS) are used to determinate the diagnosis. The system hardware consists of three distinct modules: the module of transmission and reception of ultrasound waves, the module of XY scanning to acquire the signals in several points of the calcaneus and the control module, responsible for controlling the other modules and the communication with the PC through the USB interface. The firmware for the operation of the control unit was developed for a MSP430. The system software is used by the operator to control the system and calculates the results based on the acquired waves. Through a database is possible to store information about patients, doctors and operators. This document also presents the results of tests for acrylic and evaluates the system performance.